Internet banking in Pakistan: finding complexities - Akhlaq, Mohammed ather; Shah, Asadullah (Array Development Canada (JIBC), 2011)
Technology is evolving every new day and has its impact on every thing. In this paper we will analyze the acceptance of technology in the Banking Industry of Pakisatn. This research investigates complexities (factors) that have resisted or obstructed the adoption of Internet Banking in Pakistan. Traditional innovation diffusion model (IDT) is used to develop the research model indicating the proposed complexities and acceptance of Internet Banking among Pakistani users. The model is tested with a survey sample (n=45). Out of the nine complexities identified, six are found significant. The findings of the research signify that 67 % of the proposed complexities, Familiarity with the technology, Concerns for Download Speed, Unfriendly Website Design, Fear of Government tracking transactions, Security and People Gaining Access/Misusing, hinder the users in accepting and adopting internet banking technology in Pakistan.